PTU-089 Portal Hypertensive Complications and Clinical Outcomes in Paediatric and Adolescent Patients Presenting with Portal Vein Thrombosis. (17th August 2016) - Direkze, S; Bancil, A; Dawan, A; Samyn, M; Heaton, N; Velez-Mendes, H; Davenport, M; Kane, P; Karani, J; Joshi, D
Abstract : Introduction: Portal vein thrombosis (PVT) has multiple aetiologies which can lead to the development of portal hypertension and variceal bleeding. Data on the long term sequelae of PVT in paediatric and adolescent patients is limited. Methods: Patients included had a diagnosis of PVT from Jan 2000- Dec 2014. Data collection included patient demographics, aetiologies, presentation and initial treatment of PVT. Data was also collected on further variceal bleeds, shunt surgery, liver transplantation and long term mortality. Results: 123 patients (63 male) were identified. Median age at first presentation was 5years 9 months (range 2 days to 25 years). Overall survival was 95.9, 94.3 and 93.5% at 1, 10 and >20 years from PVT diagnosis, respectively. Median age at follow up was 13years 3 months (range 6 months to 33 years 2 months). In the majority of cases (52%) no cause for PVT was identified. 78% of patients had extrahepatic PVT (EHPVT), with no extension in to the superior mesenteric vein. 19 patients (15.4%) were anticoagulated or had received a course of anticoagulation therapy. Initial presentation was usually due to oesophageal variceal bleeding (52.8%) of which 24 patients had further variceal bleeds (18.7%, oesophageal/duodenal/rectal). At follow up, 26% of patients (N = 32) were on a beta blocker. Of these, 10 patients (31.3%) had further variceal bleeds versus 14/77 patients, not on a beta blocker (18.2%, p = 0.07). Portal biliopathy was also present in 17.9% (N = 22) as was splenomegaly (82.9%). Ascites and hepatic encephalopathy were uncommon (<7%). 18 patients had shunt surgery, majority of which were meso-caval Rex, of which 7/18 (38.8%) had further variceal bleeds. Two patients underwent transplantation, one of which was for variceal bleeding. Overall mortality in this group of patient with PVT was low (6.5% N = 8) though only 2 of these patients had a previous history of recurrent variceal bleeds. Conclusion: Oesophageal variceal bleeding is a common index presentation of PVT in paediatric and adolescent patients. Approximately 20% of patients will go on to have further variceal bleeds despite medical intervention. Beta blocker use is associated with recurrent variceal bleeding which may suggest that it is ineffective in preventing further variceal bleeding in patients with established portal cavernomas. Overall, long term survival is good. Disclosure of Interest: None Declared